Indonesia dan Putaran Bali - Pradana, Adi Mulia (Global: Jurnal Politik Internasional, 2013)
The fact that "South-South" countries managed to avoid severe collapse in the global financial crisis (2007-2008) as happened in U.S. and EU, is a contradiction when the "South-South" at the same time are often disadvantaged in trade patterns. As the study of chaotic Asian crisis (1997-1998), many countries (on "South-South") are actually very disadvantaged in its main Doha Round of WTO rules, are struggling hard to optimize the productivity that can be achieved. Happened a wide selection of radical economic policies that have been and will run various countries. On one hand, there are policy options isn't enough if associated process of building solution-based collective recession settlement between states. In other words, as an effort to evaluate the regulation of international trade policy in the WTO, while adjusting needs a sense of justice for the country "South" for a dozen years caving in on WTO rules, present mometum significant change rules. Plan of Bali Round (2013) is expected to be generated in the WTO meeting in this year. Where the round is expected to not only adapt to today's trade map no longer dominated by the countries like US, EU countries, etc. But give justice a far greater for developing countries that are represented in the "South-South".